Środki retoryczne, liryka, glottodydaktyka – o zastosowaniu poezji na lekcji języka obcego - Dorota Szczęśniak, Dorota Szczęśniak (Neofilolog, 2019)
This paper discusses the importance of working with a literary text (especially poetry) in the context of the foreign language (FL) classroom. In order to facilitate FL teaching, language teachers are encouraged to use poetry and rhetorical devices occurring in such texts (e.g. rhymes, alliteration, metaphor etc.). The paper offers some teaching procedures and techniques based on rhetorical devices, which may prove valuable in raising FL students’ motivation and language awareness while having fun analyzing quality literary texts.